Pemberdayaan Komunitas Lokal Dalam Pengelolaan Limbah Plastik Sebagai Katalisator Perubahan Lingkungan dan Iklim Global - Prayitno, Budi; Panuh, Dedi Karni; Siswanto, Apri; Retno, Deddy Purnomo; Harmiyati, Harmiyati; Astuti, Puji; Luthfianto, Saufik (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to enhance the skills and participation of local communities in managing plastic waste within the Sawahlunto National Geopark area, serving as a catalyst for addressing global environmental and climate change issues. This initiative was implemented through community empowerment based on inter-institutional collaboration. Although the outcomes of community empowerment in improving plastic waste management skills and participation had not yet yielded the expected benefits for holistic economic development, the increased community understanding of plastic waste management fostered new hopes and a commendable sense of environmental concern. This success was evident in the community's active role in environmental management around key geosites through mutual cooperation activities and their growing interest in educational and research activities within the Sawahlunto National Geopark area.